2022
DOI: 10.1136/bmjopen-2021-055964
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of orthodontic treatment versus adenotonsillectomy in children with moderate obstructive sleep apnoea and mandibular retrognathia: study design and protocol for a non-inferiority randomised controlled trial

Abstract: IntroductionOrthodontic treatment and adenotonsillectomy (AT) are both conventional treatments for paediatric obstructive sleep apnoea (OSA). Each approach has distinct treatment advantages; however, there is currently a lack of solid evidence to support their efficacy comparison. We hypothesise that the objective effect of orthodontic treatment is not inferior to AT in children with moderate OSA and mandibular retrognathia, but orthodontic treatment has the advantage of promoting dentofacial growth.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Orofacial myofunctional therapy can be considered as an effective complementary treatment for OSA patients with oral breathing after adenotonsillectomy 22 . Nowadays, a randomised, open-label, parallel-group, active controlled trial was designed to study the efficacy of orthodontic treatment versus adenotonsillectomy in children with mild or moderate OSA accompanied by tonsillar adenoid hypertrophy and mandibular retrognathia [23][24] . (ClinicalTrials.gov: NCT03451318).…”
Section: Orthodontic Appliance Accompanied With Orofacial Myofunction...mentioning
confidence: 99%
“…Orofacial myofunctional therapy can be considered as an effective complementary treatment for OSA patients with oral breathing after adenotonsillectomy 22 . Nowadays, a randomised, open-label, parallel-group, active controlled trial was designed to study the efficacy of orthodontic treatment versus adenotonsillectomy in children with mild or moderate OSA accompanied by tonsillar adenoid hypertrophy and mandibular retrognathia [23][24] . (ClinicalTrials.gov: NCT03451318).…”
Section: Orthodontic Appliance Accompanied With Orofacial Myofunction...mentioning
confidence: 99%
“…MADs can expand the upper airway as well as the forward migration of the jaw and hyoid bone. Numerous studies have demonstrated the steady long-term efficacy of RME and MAD in the treatment of juvenile OSA when used in the clinical setting, such as the Frankel and Twinblock apparatus [31].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, risks from regular surgery and trauma may be connected to AT. The use of AT is a topic of intense discussion among medical experts [31].…”
Section: Discussionmentioning
confidence: 99%
“…artículos(10)(11)(12)(13)(14)(15) fueron incluidos en esta revisión sistemática, tal y como se esquematiza en la figura 1.…”
unclassified